2010
DOI: 10.1080/01402381003794647
|View full text |Cite
|
Sign up to set email alerts
|

State–Society Relationships, Social Trust and the Development of Labour Market Policies in Italy and Sweden

Abstract: The first decade of the twenty-first century may be remembered for the rebirth of consensus on labour market policy. After three decades of bitter political and ideological controversy between a neo-liberal and a traditional social democratic approach, a new model, often labelled flexicurity, has emerged. This model is promoted by numerous political organisations since it promises to put an end to the old trade-off between equality and efficiency. Several countries are embracing the flexicurity model as a blue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…It has been identified as an important determinant of high levels of job security regulations in the Nordic managed capitalist countries. Moreover, elsewhere, I have demonstrated that the labour movement is the main agent pushing for further restriction of the managerial prerogative to hire and fire (Bonoli & Emmenegger 2010; Emmenegger, 2010, Forthcoming), thereby confirming the claims of the power resources literature. However, the present analysis has also shown that strong labour movements alone (even in absence of significant institutional veto points) do not lead to extensive job security regulations.…”
Section: Discussionsupporting
confidence: 67%
“…It has been identified as an important determinant of high levels of job security regulations in the Nordic managed capitalist countries. Moreover, elsewhere, I have demonstrated that the labour movement is the main agent pushing for further restriction of the managerial prerogative to hire and fire (Bonoli & Emmenegger 2010; Emmenegger, 2010, Forthcoming), thereby confirming the claims of the power resources literature. However, the present analysis has also shown that strong labour movements alone (even in absence of significant institutional veto points) do not lead to extensive job security regulations.…”
Section: Discussionsupporting
confidence: 67%
“…The result of these complex interactions was 200 different contracts within 20 different regional regulatory frameworks and about 800 professional profiles (Di Monaco and Pilutti, 2012). In synthesis, reforms reinforced the existing fragmented landscape of actors organised at different territorial levels with diverging agendas and often lacking the institutional capacity to adequately coordinate and implement multilevel governance arrangements (Bonoli and Emmenegger, 2010), in particular in southern regions.…”
Section: Apprenticeshipmentioning
confidence: 99%
“…Second, existing research has yet to provide any support to the claims raised by the VoC literature. Based on case studies of the historical development of JSRs in Denmark, Italy, Sweden and Switzerland, Emmenegger (2010b, c) and Bonoli and Emmenegger (2010) conclude that high levels of JSRs are not the result of business interests but are forced upon employers by radicalized labour movements. However, the case studies fail to include Germany, where business support for JSRs can most likely be expected.…”
Section: Introductionmentioning
confidence: 99%